Pengaruh Budaya Kerja Islami, Komunikasi, Kompensasi, dan Lingkungan Kerja Terhadap Kinerja Karyawan dengan Motivasi Sebagai Variabel Moderating Pada PT. Bawang Mas - Putri Ayu Firawati; Holili; Mamluur Rohmah; Habibur Rohman; Rudy Haryanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Performance includes the quantity and quality of work results that employees achieve when carrying out their duties based on the responsibilities the company gives them. PT employee performance. Bawang Mas still cannot be said to be good because there are still employees who have low levels of quality and quantity of work, are not punctual, are less effective and lack commitment to the company. The aim of this research is to determine the influence of Islamic work culture, communication, compensation, individual work environment on employee performance, as well as to determine the influence of Islamic work culture, communication, compensation, work environment on employee performance which is moderated by motivation. The method in this research uses quantitative methods which are analyzed using moderating regression analysis. The population is 1,600 with a sample of 94 respondents with data obtained through a questionnaire. The results of this research are, individually, work culture Islam, communication, compensation and work environment have a significant positive effect on employee performance. Islamic work culture, communication, compensation and a work environment moderated by motivation have a significant positive effect on employee performance.